Back-contact layers on CdTe solar cells and loss analysis of top-performing devices - Kasik, Camden, author; Sites, James, advisor; Buchanan, Kristen, committee member; Harton, John, committee member; Sampath, W. S., committee member; Topič, Marko, committee member (Colorado State University. Libraries, 2025)
Photovoltaic technologies provide a nearly infinite energy source and have become cost competitive in recent years, driving them to be the most installed energy source. Cadmium telluride (CdTe) thin-film photovoltaics has the advantage of a well matched energy band-gap to the solar spectrum, as well as rapid production capabilities, making it the second most adopted solar-energy technology. Relatively low realized power conversion efficiencies, with the record being 23.1% (compared to the limit of 33%), has held CdTe back from expanding its market share. For comparison, silicon photovoltaics has reached an efficiency of 26.6% and has ~95% of the solar energy market share. The limited efficiency for CdTe is attributed in large part to the voltage deficit, which is a problem CdTe researcher have struggled with for years. Analysis to better understand the loss contributions in CdTe, and other technologies, as well as the addition of back-buffer layers will be presented in this work. Understanding the losses limiting solar-cell performance is essential to determining pathways to increased efficiencies. Comparisons to the theoretical limits of different parameters, which vary depending on the band-gap of the absorbing material, show which parameters cause different devices to have the most loss in efficiency, and thus the most room for improvement. These comparisons are done on record-efficiency devices, both single and multi-junction, from different technologies to determine which technologies have the most room for efficiency growth, and what parameter is the limiting factor. Detailed diode analysis was done to quantify the parasitic losses that negatively impact device performance. Determining these parameters produced valuable information from current-voltage data that is already available, allowing for more comparisons to be made when investigating the losses for different devices. Fill-factor losses were further analyzed using the diode parameters. The losses in fill-factor were quantified by splitting the total loss into its different diode parameter contributions. This detailed diode and fill-factor analysis gave a better understanding of what parameters caused the larger losses in photovoltaic devices. The results of this analysis on the best single-junction cells from different technologies, different CdTe laboratories, and for CdTe record devices over time are discussed. In addition to detailed loss analysis, back-buffer layers for CdTe devices were also investigated. A deposited layer of tellurium oxide was added to the native oxide present on the CdTe in the device structure as a dopant free passivating layer. Including a second CdCl2 passivation treatment was found to be crucial for good performance from the tellurium-oxide devices. Copper-doping treatments negatively impacted the device performance when additional tellurium oxide was included, with temperature-dependent current-voltage measurements suggesting the formation of an energy barrier which limited performance. Photoluminescence measurements on tellurium-oxide devices showed the impact of high-temperature treatments on absorbers with dopants already present, and the formation of defect states after an energetic sputtering deposition. Cadmium zinc telluride was also investigated as an electron-reflection layer to reduce recombination at the back surface. Optimization of the CdZnTe layer, including doping and substrate temperature, was investigated to create the best possible devices. Photoluminescence measurements, and the fact that devices including the CdZnTe layer outperformed control devices, indicated reduced recombination at the back surface. Film characterization measurements showed small crystal formation in the CdZnTe layer which highlights the importance of doping in this layer to improve conductivity for hole extraction. Experiments on First Solar absorbers again showed the impact that high-temperature processes can have on previously doped absorbers. The limitations of these back-contact layers are discussed, along with suggestions for future research to overcome them.
Keywords: interface physics; photovoltaic; cadmium telluride; thin-film; loss analysis